IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MEMBENTUK KARAKTER WIRAUSAHA SISWA KELAS IV DI SD NEGERI 2 KAMPUNG BARU - Atika Rahmawati, Astri; Agung, Putry; Nureva, Nureva; Tohir, Ahmat (Berajah Journal, 2024)
The project to strengthen the Pancasila student profile is one means of achieving the Pancasila student profile, which provides opportunities for students to understand knowledge as a process to strengthen character and provide opportunities to learn from the surrounding environment. The type of research used is qualitative research with a descriptive type. This research was conducted at SD Negeri 2 Kampung Baru in class IV. Data collection techniques in this research are observation, interviews and documentation. The subjects of this research were the principal, class IV teachers and class IV B students. Based on the research results, it can be concluded that the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) at SD Negeri 2 Kampung Baru, which is one part of the independent curriculum structure, has been implemented well. after going through planning, implementation and assessment. implementing the project with an entrepreneurial theme that can shape students' entrepreneurial character, because students are taught to make products that have selling value. By implementing this project, the character of being creative, critical reasoning and working together is instilled in students.